Role of Tissue-Resident Memory in Intra-Tumor Heterogeneity and Response to Immune Checkpoint Blockade - Dhodapkar, Kavita M. (Frontiers in Immunology, 2018)
Tissue resident memory T (TRM) cells are a distinct subset of memory T cells that reside in peripheral tissue for prolonged periods of time without significant recirculation providing continued immune surveillance at these sites. Recent studies suggest that TRM cells are also enriched within tumor tissue. Expression of inhibitory immune checkpoints is particularly enriched on this subset of tumor-infiltrating T cells, suggesting that they are major targets for newer therapies targeting immune checkpoints such as the programmed death-1 (PD-1) pathway. Recent studies suggest that tissue restriction of these cells without recirculation may also lead to heterogeneity of TRM cells within individual metastatic lesions, ultimately leading to interlesional diversity. Thus, individual metastatic lesions may contain genomically distinct immune microenvironments that impact both evolution of tumors as well as the mechanisms underlying response and resistance to immune therapies. Understanding the biology of TRM cells infiltrating tumors will be essential to improving immune-based approaches in diverse settings